Temperature Dependency of Photoelectronic Properties of Group III-V Arsenide Solar Cell - Al Humayun, Md. Abdullah; Hossen, Masum; Haider, Md. Zamil; Yousif, Bedir; Chughtai, Muhammad Tajammal; Islam, Muhammad; Khan, Sheroz (Engineering, Technology & Applied Science Research, 2024)
This study explores the effect of temperature on different characteristics of Solar Cells (SC) composed of a structured III-V arsenide group. The temperature dependence of the SC characteristics was investigated numerically and by simulation. In both approaches, each characteristic was compared with a conventional Si SC. InAs showed superior stability and lower temperature sensitivity, as it has a negligible decrease of 0.098 eV in the energy bandgap, while the energy bandgaps of Si, AlAs, and GaAs are 0.129, 0.186, and 0.200 eV, respectively. Moreover, with a decay rate of 81.911 mV/°K, InAs exhibited the lowest temperature sensitivity in open-circuit voltage. InAs additionally demonstrated the least increase in degradation rate, while the SC power output is still a cause of concern. AlAs, Si, and GaAs had a total accumulative gradient change of 0.162, 0.136, and 0.034% in the degradation rate, respectively, while InAs showcased the highest stability by displaying a change of only 0.008%. A comparative analysis illustrated that among these III-V arsenide compounds, InAs had a rock-bottom sensitivity to temperature changes and better temperature stability in both numerical and simulation approaches.